MiCoTaph. Fossil Micromammals from Cooper’s Cave (Lower Pleistocene, South Africa): contribution to a better knowledge of the taphonomic and environmental context of Paranthropus robustus occupations. - (:unkn) unknown (My University, 2019)
The simultaneous presence of several hominin species in South Africa during the Plio-Pleistocene, especially the first representatives of the genus Homo, Paranthropus and possibly late surviving Australopithecines, makes it difficult to understand the evolutionary history of these lineages, as well as their technical and subsistence behaviors. It then appears necessary to better characterize the occupations related to each species, and in particular the environment in which each of them has evolved. Small mammals such as rodents are good palaeoecological markers, but remain poorly studied in early hominin sites in South Africa. In order to understand the evolutionary dynamics of this time, the MiCoTaph project aims to reconstruct the taphonomic and palaeoenvironmental context of the Paranthropus robustus occupations of Cooper's D (Bloubank Valley, South Africa, < 1.4 Ma). An interdisciplinary approach is applied using taxonomic, taphonomic and palaeoecological methods to analysis the micromammal remains.
Keywords: African Research